PESTISIDA NABATI DAUN PEPAYA UNTUK PERTANIAN BERKELANJUTAN DAN PRODUKTIVITAS DI DESA GUMUK, BANYUWANGI - Herlambang, Bagus; Hariyadi, Edy; Alfianti, Selfi; Putri, Bella Ayu Widya; Rizkiana, Waheda Budi; Viola, Imelda Indra; Pitaloka, Diah Ayu; Altamarix, Nabila Risqita; Dewi, Lyca Shelya; Maulana, Muhammad Ilham; Hayata, Schatzi Bintang; Indriyawati, Vhiranita Audrey; Basuki, Ferry Hendro (PAPUMA: Journal of Community Services, 2026)
This community service program, implemented by Universitas Jember in Gumuk Village, Licin District, Banyuwangi, focuses on the development of sustainable industrial agriculture through the use of papaya leaf-based biopesticides (PEPACIDA). The program was conducted using a participatory approach involving observation, training, and direct mentoring of local farmers. Papaya leaves (Carica papaya L.), combined with garlic, were processed into a liquid biopesticide and tested on rice and corn plants. The results showed significant effectiveness in reducing pest attacks such as Spodoptera frugiperda (Army caterpillar), Leptocorisa acuta (grasshopper), and Fulgoroidea (planthopper) without leaving harmful residues in the environment. Farmers reported increased awareness of environmentally friendly practices and reduced dependence on chemical pesticides. This initiative not only increased agricultural productivity but also encouraged environmental conservation and local self-reliance in pest control management.